Nematode-Infected Mice Acquire Resistance to Subsequent Infection With Unrelated Nematode by Inducing Highly Responsive Group 2 Innate Lymphoid Cells in the Lung - Yasuda, Koubun; Adachi, Takumi; Koida, Atsuhide; Nakanishi, Kenji (Frontiers in Immunology, 2018)
In tropical and subtropical regions, the distributions of many helminthic diseases overlap with one another. The immune responses against helminths have been investigated individually, and it is well-established that infected hosts develop an immunological memory to resist reinfection by the same pathogen. In contrast, it is poorly understood how the host immune system responds to subsequent infection by unrelated parasites after elimination of the first infection. We previously reported that infection of mice with Strongyloides venezuelensis induces the accumulation of group 2 innate lymphoid cells (ILC2s) in the lung. Here, we found that S. venezuelensis-experienced (Sv-exp) mice became significantly resistant against infection by Nippostrongylus brasiliensis, and this resistance was dependent on IL-33, ILC2s, and eosinophils but not on CD4+ T cells. ILC2s in Sv-exp mice acquired a highly responsive “trained” phenotype; they rapidly increased and produced IL-5 and IL-13 in response to N. brasiliensis infection. In conclusion, S. venezuelensis-infected hosts acquire a specific-antigen-independent resistance to lung-migrating nematodes.